Influence of Land Use and Climate on the Load of Suspended Solids in Catchments of Andean Rivers - Pizarro-Konczak, J; Vergara-Egert, P (2014)
Understanding the interaction between anthropogenic land use and the rainfall pattern can be crucial to predict changes in total suspended solids (TSS) in streams and rivers. We assessed the effects of land use and annual rainfall on the TSS load of 19 southern Chilean catchments. The results indicated that the concentration of TSS increased in catchments with a rainy regime and greater annual precipitation. TSS load also increased as the surface of open areas increased at the catchment scale and decreased with increasing cover of glaciers and perennial snow. However, we did not find support for models with interaction terms between climate and land use. Results suggest that a regional decrease in annual rainfall accompanied by an increase in the altitude of the zero isotherms, as predicted by climate models, should have multiple effects on TSS. In particular, increased TSS load can be expected from a contraction of glaciers and perennial snow areas as well as the intensification of new crops and urban expansion. © 2013 Springer Science+Business Media Dordrecht.